2019
DOI: 10.1155/2019/1471879
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Scoliosis in a Child with Cystic Fibrosis

Abstract: We discuss an adolescent female with cystic fibrosis, asthma, and scoliosis who had a rapid decline in her pulmonary function despite typical treatment for a cystic fibrosis exacerbation. Ultimately, she had a fixed airway obstruction likely due to her progressive scoliosis, which improved following surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The chronological classification is important in quantifying the risk of developing a more severe and complicated deformity, while the angular classification is crucial in the management of IS since it is directly correlated with treatment decisions [ 16 , 17 , 18 ]. Scoliosis in CF has been previously investigated [ 11 , 14 , 19 , 20 , 21 , 22 ], and most authors have found that in these patients its prevalence is higher compared to the healthy population, where the prevalence ranges from 0.2 to 2.2% with a preference for girls, especially in older age and when the curve is higher [ 23 , 24 ]. On the other hand, kyphosis is an excessive curvature of the thoracic spine in the standing position.…”
Section: Introductionmentioning
confidence: 99%
“…The chronological classification is important in quantifying the risk of developing a more severe and complicated deformity, while the angular classification is crucial in the management of IS since it is directly correlated with treatment decisions [ 16 , 17 , 18 ]. Scoliosis in CF has been previously investigated [ 11 , 14 , 19 , 20 , 21 , 22 ], and most authors have found that in these patients its prevalence is higher compared to the healthy population, where the prevalence ranges from 0.2 to 2.2% with a preference for girls, especially in older age and when the curve is higher [ 23 , 24 ]. On the other hand, kyphosis is an excessive curvature of the thoracic spine in the standing position.…”
Section: Introductionmentioning
confidence: 99%